TRUST FACTOR ON KNOWLEDGE-SHARING BEHAVIOUR AMONG LAWYERS IN KUALA LUMPUR: AN ANALYSIS - Alwi Mohd Yunus; Zulkifli Mohammed; Jannatul Iza Ahmad Kamal; Mohd Ridwan Kamarulzaman; Rahmawati Mohd Yusoff (Journal of Islamic, Social, Economics and Development, 2024)
Legal firms are probably the place where knowledge is freely and openly shared among the lawyers. Although, knowledge sharing is hardly presented within the legal firm these days in reality. The legal profession, particularly law firms, is currently dealing with an increase in the number of individuals prosecuted in court, as well as the passage of new legislation and modifications by Parliament, all of which necessitate the pooling of quality expertise and resources. The goal of the study was to determine the elements that influence information sharing among lawyers in Kuala Lumpur. The study looked at the idea of information-sharing behavior from the perspective of a lawyer, looking at the aspects of expected benefits, expected affiliation, and expected contribution, as well as tacit knowledge sharing of knowing how. The relationship between trust and knowledge sharing behavior has also been examined using the social exchange theory. The study identified trust as a critical component that motivates a business to invest in valued resources. Knowledge, on the other hand, is regarded as a source of strength and an indisputable feature. Humans and knowledge-sharing behavior are the two fundamental components of knowledge. The theoretical appraisal of how lawyers are disposed positively toward knowledge exchange inside the legal firm and contribute to the legal profession is presented in this study. It is critical to aid lawyers in developing and promoting a knowledge-sharing environment, particularly within the legal community in Kuala Lumpur, Malaysia.